Association Between IFN-?4 rs12979860 And rs11322783 Polymorphisms with Spontaneous Clearance In Chronic Hepatitis B - Özkan, Fariz Emrah; Dalkilic, Semih; Dalkilic, Lütfiye Kadioglu; Sahin, Abdurrahman; Bahçecioğlu, İbrahim Halil; Yalniz, Mehmet (My University, 2025)
Many studies have been published on the association between IFN-?3 and IFN-?4 polymorphisms and treatment related or spontaneous clearance of chronic hepatitis C. To date there is little known about the impact of IFN-?4 polymorphisms on the natural history of chronic hepatitis B(CHB). This study aimed to investigate the role of IFN-?4 polymorphisms on the course of CHB and to influence the presence of spontaneous clearance (SC) in CHB patients. One hundred and twenty-two patients who had CHB, and 81 subjects who had spontaneous resolution of HBV were analyzed regarding IFN-?4 rs12979860 and rs11322783 single nucleotide polymorphisms. We couldn’t found any significant difference between CHB groups and SC groups in terms of IFN-?4 rs12979860 polymorphisms and, the CC, C/T and TT genotypes represented 49%, 45% and 5% of CHB patients and, %46, 43% and 11% of SC group respectively (p=0.65). On the other hand, in IFN-?4 rs11322783 polymorphisms analysis, recessive G/G allele was more common in SC group compared to CHB group (5% vs 16%, p=0.04; OR: 3,55). Moreover, non-G/G genotypes had significantly higher in CHB patients compared to SC group (95% vs 84%, p=0.013; OR:3.55). Our results suggest that IFN-?4 rs11322783 polymorphism may be a predictor of spontaneous clearance in HBV infected patients. The role of IFN-?4 polymorphisms needs to be investigated in the natural history of HBV.
Keywords: Hepatitis B virus; Single nucleotide polymorphism; Interferon-?4; Spontaneous clearance